THE EFFECT OF COMMUNICATION, SELF-EFFICACY AND POWER ON THE COMMITMENT OF EMPLOYEES - Ie, Mei; Maupa, Haris; Madris, Madris (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of communication, self-efficacy and power on the commitment of employees of PT XYZ. This research was conducted using a descriptive quantitative approach through survey techniques. The sample used amounted to 65 respondents came from employees of PT XYZ. Data analysis was performed using Partial Least Square – Structural Equation Model (PLS-SEM) using smartPLS 3.0 software. The results showed that communication, self-efficacy and power had a positive and significant influence on employee commitment at PT XYZ. This shows that if there is an increase or improvement in communication, self-efficacy and power are able to maintain and even increase employee commitment to the company, namely PT XYZ.. The thing that needs to be considered for the company is to pay attention and keep employees having high confidence in facing work challenges. Because of communication, self-efficacy, and power influence on the employees commitment, this research has theoretically and practically implication. Theoretically, employees commitment be created through how to build a good communication, notice the employees self-efficacy, and positive power implementation. Meanwhile for practically implication, management of PT XYZ could use this research as a hint of company policy making.